Diskursus Hermeneutik dalam Paradigma Keislaman dan Kemodernan - Nurkhalis Nurkhalis (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2015)
Muslim scholars’ interests on hermeneutic have led to the development of the Al-Quran interpretation into various models. Hermeneutic has become the icon in modernization of Al-Quran values in which interpretation revolves around transnational and multidimensional perspectives which are sometimes political to advocate humanism, feminism, and pluralism. Based on the literature review, the interpretation of Al-Quran tends to lead to some typologies namely constructive, pro-constructive, reconstructive and deconstructive typologies. The hermeneutic in the constructive typology was introduced by a'immah al-‘arba’ah scholars such as Hanafi, Syafi’i, Hambali and Maliki. Meanwhile, the pro-constructive typology was led by Ghazali, Ibnu Qayyim al-Jauzi, lmam Shatibi, Muhammad ‘Abid al-Jabiri and At-thabari. The hermeneutic in the reconstructive typology was introduced by Ibnu Taimiyah, Muhammad 'Abduh, Hasan Hanafi, Fazlur Rahman, Sayyed Hossein Nasr, Khaled M. Abou al-Fadl and Yusuf Qaradhawi. The hermeneutic in the deconstructive typology refers to the hermeneutic introduced by Arkoun, Muhammad Shahrour, Nasr Hamid Abu Zaid, Abdullah An-Na’im, Amina Wadud, Fatema Memissi, and Asma Barlas.